Regulatory T cell-mediated anti-inflammatory effects promote successful tissue repair in both indirect and direct manners - Lei, Hong; Schmidt-Bleek, Katharina; Dienelt, Anke; Reinke, Petra; Volk, Hans-Dieter (Frontiers in Pharmacology, 2015)
Regulatory T cells (Treg) offer new immunotherapeutic options to control undesired immune reactions. In addition, tissue repair and regeneration depend on a multitude of tightly regulated immune and non-immune cells and signaling molecules. There is mounting evidence that adequate innate responses, and even more importantly balanced adaptive immune responses, are key players in the tissue repair and regeneration processes, even in absence of any immune-related disease or infection. Thus, the anti-inflammatory and anti-apoptotic capacities of Treg can affect not only the effector immune response, creating the appropriate immune environment for successful tissue repair and regeneration, but growing evidence shows that they also have direct effects on tissue cell functions. Here we summarize the present views on how Treg might support tissue regeneration by direct control of undesired immune reactivity and also by direct interaction with non-immune tissue cells. We describe tissue-resident Treg and their specific phenotypes. We also touch on the topic of osteoimmunology, discussing the direct interactions of Treg with bone-forming cells, such as osteoblasts and their mesenchymal stromal cell (MSC) progenitors. We hypothesize cross-talk between Treg and bone-forming cells through the CD39-CD73-(adenosine)-adenosine receptor (ADOR) pathway, which might also potentiate the differentiation of MSCs, thus facilitating bone regeneration.